2010
DOI: 10.1016/j.addr.2010.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Engineering RNA for Targeted siRNA Delivery and Medical Application

Abstract: RNA engineering for nanotechnology and medical applications is an exciting emerging research field. RNA has intrinsically defined features on the nanometer scale and is a particularly interesting candidate for such applications due to its amazing diversity, flexibility and versatility in structure and function. Specifically, the current use of siRNA to silence target genes involved in disease has generated much excitement in the scientific community. The intrinsic ability to sequence-specifically down-regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
181
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(193 citation statements)
references
References 198 publications
(264 reference statements)
2
181
0
10
Order By: Relevance
“…Aptamers are a family of RNA-or DNA-based oligonucleotides 20-50 nt in length that can specifically bind to selected targets (Guo, et al, 2010). They have often been described as nucleic acid versions of antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Aptamers are a family of RNA-or DNA-based oligonucleotides 20-50 nt in length that can specifically bind to selected targets (Guo, et al, 2010). They have often been described as nucleic acid versions of antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Oligonucleotide therapies using microRNA (miRNA), small interfering RNA (siRNA), or ribozyme have attracted particular attention because of their specificity and safety. [2][3][4] miRNAs, a class of small non-coding single-stranded RNAs that are 20-22 nucleotides long, are involved in multiple cellular biological processes, such as differentiation, proliferation, apoptosis, and migration by targeting the 3′ untranslated region (UTR) of mRNAs of target genes in a sequence-specific manner. [5][6][7] It has also been shown that miRNAs have a crucial role in carcinogenesis and cancer progression.…”
mentioning
confidence: 99%
“…The most obvious use of oligonucleotide nanostructures in the medical field is the delivery of siRNA, antisense RNA or genes. However, several excellent reviews on this topic have been published recently [44][45][46][47]. The same holds true for DNA nanoobjects employed in the context of cellular and in-vivo bioimaging [48,49].…”
Section: Introductionmentioning
confidence: 97%